Building The Research Disposition Of Teachers Through Pedagogical Documentation - Maldonado Ruiz, Gonzalo; Soto-Gómez, Encarnación (My University, 2019)
This research, supported by the University of Malaga and Spanish Government (FPU 17/03577), incorporates the concept of practical knowledge to understand the complexity of the teaching profession and, therefore, its evolution (Pérez Gómez, 2012, 2017). We understand practical knowledge as the conglomerate of attitudes, emotions, values, skills and knowledge that are put into play, automatically and unconsciously, in action and educational analysis (the so-called theories in use by Argyris, 1982). Therefore, we need to incorporate experiences in teacher training that make visible, mobilize and make possible the reconstruction of this practical knowledge through reflective and inquiry processes. When this process takes place, we can affirm that teachers are reconstructing their knowledge and experiences through the development of practical thinking. This concept refers to the "conscious, reflective, contrasted and reposed reconstruction, of this same system of understanding and action that includes both knowledge in action and reflexive knowledge about the action" (Pérez Gómez, 2017, p.17). How can we design experiences that promote the development of practical thinking and incorporate research on one's own practice in teacher education? From this point of view, this paper shows part of an investigation that seeks to know in what sense, introducing pedagogical documentation as a methodological axis in the Degree in Early Childhood Education, makes visible and mobilizes pre-service teacher’s practical knowledge. We understand the pedagogical documentation as a systematic collection and exposition process (Hoyuelos, 2013) of photographs, recordings, materials, videos, conversations, etc. that enlighten "flashes in the complexity of learning and students" (Krechevsky, Mardell, Rivard, & Wilson, 2013, p.58)
Keywords: Pedagogía -- Documentación; Pedagogical Documentation; Practical Knowledge; Early Childhood Education; Research Disposition; Reflection